Faraday rotation in cryogenically cooled dysprosium based (Dy2O3) ceramics. (1st March 2019) - Yakovlev, Alexey; Snetkov, Ilya; Permin, Dmitry; Balabanov, Stanislav; Palashov, Oleg
Abstract: The temperature dependences of a Verdet constant of ceramic samples with the compositions (Dy x Y0.95− x La0.05 )2 O3, x = 0.7, 0.85, 0.9 and their approximations in the temperature range 80–294 K and in the wavelength range 405–1064 nm were obtained with the <10% deviation from the experimental data. Cryogenic cooling leads to increase the Verdet constant value, proportional to inverse temperature, which allows to shorten a magneto–optical element length in cryogenic Faraday isolators. Results obtained are necessary for developing of Faraday devices for Tm 3+ and Ho 3+ lasers, and for lasers operating in the visible spectral region. Graphical abstract: